To grow or not to grow under nutrient scarcity: Target of rapamycin-ethylene is the question - García, María José; Angulo, Macarena; Lucena, Carlos; Pérez-Vicente, Rafael; Romera, Francisco Javier (Frontiers in Plant Science, 2022)
To cope with nutrient scarcity, plants generally follow two main complementary strategies. On the one hand, they can slow down growing, mainly shoot growth, to diminish the demand of nutrients. We can call this strategy as ‘stop growing’. On the other hand, plants can develop different physiological and morphological responses, mainly in their roots, aimed to facilitate the acquisition of nutrients. We can call this second strategy as ‘searching for nutrients’. Both strategies are compatible and can function simultaneously but the interconnection between them is not yet well known. In relation to the ‘stop growing’ strategy, it is known that the TOR (Target Of Rapamycin) system is a central regulator of growth in response to nutrients in eukaryotic cells. TOR is a protein complex with kinase activity that promotes protein synthesis and growth while some SnRK (Sucrose non-fermenting 1-Related protein Kinases) and GCN (General Control Nonderepressible) kinases act antagonistically. It is also known that some SnRKs and GCNs are activated by nutrient deficiencies while TOR is active under nutrient sufficiency. In relation to the ‘searching for nutrients’ strategy, it is known that the plant hormone ethylene participates in the activation of many nutrient deficiency responses. In this Mini Review, we discuss the possible role of ethylene as the hub connecting the ‘stop growing’ strategy and the ‘searching for nutrients’ strategy since very recent results also suggest a clear relationship of ethylene with the TOR system.